2015
DOI: 10.1001/jamasurg.2015.2644
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Endovascular vs Open Aortic Aneurysm Repairs

Abstract: The survival advantage for EVAR repair in a statewide population is maintained for 3 years. After 3 years, EVAR repair was associated with higher mortality; however, these mortality differences did not reach statistical significance over the entire study period. Reintervention and late AAA rupture rates are higher after EVAR repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 13 publications
4
39
1
1
Order By: Relevance
“…We defined this complication as a pulmonary consolidation on radiography with positive bronchoaspirate. Pneumonia more often occurred after OAR, 17 mostly in those patients requiring longer invasive ventilation. In some of these patients, a renal impairment could be included in a wider multiorgan failure, which can partly explain the concomitance of these two complications.…”
Section: Discussionmentioning
confidence: 98%
“…We defined this complication as a pulmonary consolidation on radiography with positive bronchoaspirate. Pneumonia more often occurred after OAR, 17 mostly in those patients requiring longer invasive ventilation. In some of these patients, a renal impairment could be included in a wider multiorgan failure, which can partly explain the concomitance of these two complications.…”
Section: Discussionmentioning
confidence: 98%
“…Several authors have reported rates of readmission after individual vascular procedures, such as abdominal aortic aneurysm repair (8%-54%), [14][15][16] amputation (9%-18%), [17][18][19] and lower extremity bypass (12%-49%). 8,9,11,20,21 However, there are conflicting reports regarding readmission rates and reasons.…”
Section: Discussionmentioning
confidence: 99%
“…EVAR should be a preferred method of surgical treatment of both elective and ruptured AAA (11). However, in long-term observation both methods of AAA repair were comparable (26). The latest outcomes reported from Asia have not identified significant difference between the EVAR and OAR (27,28,30).…”
Section: Discussionmentioning
confidence: 90%
“…However was no significant difference in long-term survival between both methods of AAA repair over the entire study period and after 3 years even EVAR was associated with higher mortality (hazard ratio, 0.99; 95% CI, 0.94 -1.04; p = 0.64). Moreover endovascular method was also related to higher rate of re-interventions and AAA late ruptures (26).…”
Section: Endovascular Aneurysm Repair or Open Aneurysm Repair For Thementioning
confidence: 97%